2004
DOI: 10.1023/b:biop.0000047141.49470.77
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Anatomical Structure and Lignin Content of Roots of pedunculate Oak and Wild Cherry-Tree Plantlets During Acclimation

Abstract: The lignin contents and anatomical structure of roots of wild cherry (Prunus avium L.) and pedunculate oak (Quercus robur L.) plantlets were compared to explain differences in response during transfer from in vitro to ex vitro conditions. Lignification of cell walls increased significantly in both oak and cherry roots during the period of acclimation and finally lignin content of root tissues of in vitro propagated plantlets reached the levels not significantly different from seedlings grown in soil. Later on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
2
30
0
1
Order By: Relevance
“…; Radiculites type (Strullu-Derrien et al 2009) Ginkgoaceae Ginkgo biloba (Gerrath et al 2002) Taxaceae Taxus cuspidata (Gerrath et al 2002), T. baccata (Van Tieghem 1871; Von Guttenberg 1961) Torreya nucifera (Van Tieghem 1888) Cupressaceae Callitris quadrivalvis (Noelle 1910) Chamaecyparis lawsoniana, C. obtuse, C. pisifera, C. sphaeroidea (Noelle 1910) Cryptomeria japonica (Gerrath et al 2002;Noelle 1910) Cunninghamia lanceolata (Gerrath et al 2002), C. sinensis (Noelle 1910) Cupressus macrocarpa, C. sempervirens (Noelle 1910) Juniperus virginiana (Gerrath et al 2002), J. communis, J. chinensis, J. excelsa, J. nana, J. sabina (Noelle 1910) Libocedrus decurrens (Noelle 1910;Wilcox 1962) Sciadopitys verticillata (Noelle 1910) Sequoiadendron gigantea (Gerrath et al 2002), S. sempervirens (Noelle 1910;Von Guttenberg 1961) Taxodium distichum (Noelle 1910) Thuja occidentalis (Gerrath et al 2002;Van Tieghem 1888;Brundett et al 1990), T. orientalis, T. plicata, T. standishii (Noelle 1910) Rosaceae Prunus avium L. (Soukup et al 2004) Prunus dulcis  P. persica (Marin et al 2009) Eriobotrya japonica Lindl. (Nii et al 2004;Pan et al 2006) Malus domestica (Mackenzie 1979;Weerdenburg and Peterson 1983) Pyrus communis (Essau 1943) Dryas integrifolia Vahl.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…; Radiculites type (Strullu-Derrien et al 2009) Ginkgoaceae Ginkgo biloba (Gerrath et al 2002) Taxaceae Taxus cuspidata (Gerrath et al 2002), T. baccata (Van Tieghem 1871; Von Guttenberg 1961) Torreya nucifera (Van Tieghem 1888) Cupressaceae Callitris quadrivalvis (Noelle 1910) Chamaecyparis lawsoniana, C. obtuse, C. pisifera, C. sphaeroidea (Noelle 1910) Cryptomeria japonica (Gerrath et al 2002;Noelle 1910) Cunninghamia lanceolata (Gerrath et al 2002), C. sinensis (Noelle 1910) Cupressus macrocarpa, C. sempervirens (Noelle 1910) Juniperus virginiana (Gerrath et al 2002), J. communis, J. chinensis, J. excelsa, J. nana, J. sabina (Noelle 1910) Libocedrus decurrens (Noelle 1910;Wilcox 1962) Sciadopitys verticillata (Noelle 1910) Sequoiadendron gigantea (Gerrath et al 2002), S. sempervirens (Noelle 1910;Von Guttenberg 1961) Taxodium distichum (Noelle 1910) Thuja occidentalis (Gerrath et al 2002;Van Tieghem 1888;Brundett et al 1990), T. orientalis, T. plicata, T. standishii (Noelle 1910) Rosaceae Prunus avium L. (Soukup et al 2004) Prunus dulcis  P. persica (Marin et al 2009) Eriobotrya japonica Lindl. (Nii et al 2004;Pan et al 2006) Malus domestica (Mackenzie 1979;Weerdenburg and Peterson 1983) Pyrus communis (Essau 1943) Dryas integrifolia Vahl.…”
mentioning
confidence: 99%
“…The chemical composition of phi thickening has been analysed using specific dyes for cell wall components, such as phloroglucinol for lignin or Sudan III for suberins. Some authors have observed that phi thickenings have abundant content of lignins (Haas et al 1976;Soukup et al 2004) and can be significantly lignified after environmental stresses (Fernandez-Garcia et al 2009;Henrique et al 2010). Suberin is typically found in the endodermal cells, but has not been found in the phi thickenings.…”
mentioning
confidence: 99%
“…In addition, phi-thickenings were formed in the cortical cells close to the endodermis. Soukup et al (2004) described a similar phenomenon in wild cherry where phi-thickenings appeared after acclimatization (they did not studied in vivo formed roots), but they did not found differences after acclimatization in other characters. After root maturation, secondary roots can appear from the stele, and in the base of the root, the vascular cylinder contained thicker and highly lignified xylem vessels protected by suberinized cell layers while the cortical cells showed little intercellular adherence.…”
Section: Acclimatized Rootsmentioning
confidence: 86%
“…Here, the presence of phithickening in both in vivo roots and in vitro roots after acclimatization, together to their absence in in vitro roots, suggests that their role can be related to water transport and root functioning. Moreover, phi-thickenings are present only in the maturation zone (Soukup et al, 2004), where simultaneously appeared root hairs and mature xylem vessels.…”
Section: In Vitro Rootsmentioning
confidence: 99%
“…Soukup et al (2004) também observaram que diferentemente do que ocorria na condição de solo, Prunus avium L. não desenvolvia espessamento em fi quando cultivada in vitro. Evidências relacionadas ao habitat natural que indicam que o espessamento em fi pode ser importante no processo de penetração de raízes foram relatadas por Larson et al (2000), os quais observaram que 20 dentre 26 espécies de gimnospermas estudadas, de ocorrência natural em solo com elevado grau de impedimento à penetração de raízes, apresentavam espessamento em fi.…”
Section: Variadas Funções Do Espessamento Em Fiunclassified